Dental intrusion in deciduous dentition. Report of a clinical case - Padilla-Cáceres, Tania; Granda-Rivera, Bryans; Peralta-Choque, Jimy; Acero-Condori, Lizbeth (Revista Acciones Médicas, 2023)
Injuries such as dental dislocations are frequent in children, since these are the result of traumatisms that could occur, accompanied on many occasions by dental intrusion which may or may not affect the permanent dental germ, these must be treated quickly and in the most atraumatic and conservative as possible, based on its degree of severity, in order to avoid possible sequelae. A 2-year-old male patient who comes to a private practice due to trauma in the upper anterior dental region is described. On examination, little visibility of the dental piece is observed 5.1. Based on the clinical examination, inflammation is seen in the area, as well as a slight rotation of the dental piece; the radiographic examination does not show damage to the permanent tooth germ. A pharmacological treatment was carried out and the dental re-eruption itself was awaited, after a follow-up for 3 weeks no sequelae were observed. The patient presented an uneventful evolution, timely treatment was essential for a good prognosis.